Using Mind Mapping Strategy In Teaching Descriptive Writing To The Tenth Grade Students Of SMK Budi Mulia Utama - Sanjaya, Meggy; Miftakh, Fauzi; Saefullah, Hilmansyah (Universitas Pahlawan Tuanku Tambusai, 2025)
This study adopts a qualitative approach and employs an observational research design. The objectives of this research are: (1) to investigate how the teacher implements the mind mapping strategy in teaching descriptive texts, and (2) to assess students’ abilities in writing descriptive texts using the mind mapping strategy. The findings of this study reveal two main points. First, the teacher effectively implemented the teaching of descriptive texts using the mind mapping strategy in alignment with pedagogical principles. Second, the students’ performance in writing descriptive texts using the mind mapping strategy was considerably lacking. Nearly all students failed to construct mind maps that adhered to the structure and examples demonstrated by the teacher. Only one or two students successfully created mind maps that reflected the proper format and conventions. Most students produced disorganized visuals, which suggests several possible contributing factors, such as limited prior knowledge, inadequate writing practice, low motivation, or difficulty transferring ideas from visual mind maps into coherent written texts.